A new approach to assess inflation expectations anchoring using strategic surveys - Olivier Armantier; Argia M. Sbordone; Giorgio Topa; Wilbert Van der Klaauw; John C. Williams (Federal Reserve Bank of New York, 2022)
We propose a new approach to assessing the anchoring of inflation expectations using "strategic surveys". Namely, we measure households' revisions in long-run inflation expectations after they are presented with different economic scenarios. A key advantage of this approach is that it provides a causal interpretation in terms of how inflation events affect long-run inflation expectations. We implement the method in the summer of 2019 and the spring-summer of 2021 when the anchoring of long-run inflation expectations was in question. We find that the risk of unanchoring of expectations was reasonably low in both periods, and that long-run inflation expectations were essentially as well anchored in August 2021 as in July 2019, before the COVID-19 pandemic.
Keywords: D12; D84; E31; E52; 330; inflation; expectations; anchoring; strategic surveys